2013
DOI: 10.1007/s11103-013-0129-x
|View full text |Cite
|
Sign up to set email alerts
|

The maize d2003, a novel allele of VP8, is required for maize internode elongation

Abstract: The d2003 is a natural dwarf mutant from maize inbred line K36 and has less than one-third of K36 plant height with severely shortened internodes. In this study, we reported the cloning of d2003 gene using positional cloning. The results showed that there was a single-base insertion in the coding region of Viviparous8 (VP8) in d2003 mutant, which resulted in a premature stop codon. Further genetic allelism tests confirmed that d2003 mutation is a novel allele of VP8. VP8 is mainly expressed in the stem apex, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…These genes, preferentially expressed in response to internal and external stimuli, can trigger a wide range of developmental processes in plants. For example, Zm.5799.1.A1_at upregulation enhances antioxidants in maize [45] , implying that these are excellent candidates for involvement in the biosynthetic processes and cellular organization of internodes.…”
Section: Stress-responsive Genesmentioning
confidence: 99%
“…These genes, preferentially expressed in response to internal and external stimuli, can trigger a wide range of developmental processes in plants. For example, Zm.5799.1.A1_at upregulation enhances antioxidants in maize [45] , implying that these are excellent candidates for involvement in the biosynthetic processes and cellular organization of internodes.…”
Section: Stress-responsive Genesmentioning
confidence: 99%
“…In contrast to other mutants with deregulated shoot meristem activity, amp1 SAM size normalizes after floral transition, and altered shoot meristem activity appears to be limited to decreased apical dominance (Vidaurre et al, 2007). Mutants of AMP1 orthologs in Zea mays, rice (Oryza sativa), and Lotus japonicus generate comparable SAM defects, indicating that the function of this factor in respect to shoot development is conserved among higher plants (Suzuki et al, 2008;Kawakatsu et al, 2009;Suzaki et al, 2013;Lv et al, 2014).…”
mentioning
confidence: 99%
“…ZmMADS69 has higher expression levels in temperate compared to tropical germplasm, leading to significant detection in temperate by tropical crosses [52], such as LH82xLAMA among others [23, 24, 53]. The identified region on chromosome 1 contained the viviparous8 (vp8; GRMZM2G010353; Chr1: 286390345..286398537) locus which exhibits dwarfism due to reduced cell proliferation [54]. Both loci may be deterministic QTL (dQTL) because the differential allelic variation affected the whole growth process [55] and was unaffected by environmental stimuli; ZmMADS69 effect was not influenced by day length [52] and vp8 exhibited normal plant hormone response [54].…”
Section: Resultsmentioning
confidence: 99%
“…The identified region on chromosome 1 contained the viviparous8 (vp8; GRMZM2G010353; Chr1: 286390345..286398537) locus which exhibits dwarfism due to reduced cell proliferation [54]. Both loci may be deterministic QTL (dQTL) because the differential allelic variation affected the whole growth process [55] and was unaffected by environmental stimuli; ZmMADS69 effect was not influenced by day length [52] and vp8 exhibited normal plant hormone response [54]. These results coupled with basic biological understanding indicated that allelic changes in loci can have a fundamental impacts on the functional growth trajectory of maize, in contrast to the small shift in phenotypic expression of a single trait It is therefore understandable that these two “major genes” have been previously identified and described in multiple studies, while the smaller and ephemeral effect loci are mostly unknown.…”
Section: Resultsmentioning
confidence: 99%